Quantitative literacy of school leavers aspiring to higher education in South Africa - Frith, V; Prince, R (South African Journal of Higher Education, 2016)
It is important for higher education educators to understand the quantitative literacy (QL) competencies of incoming students, in order to make appropriate assumptions about prior knowledge and to design suitable curricula. In this paper we analyse the results of a National Benchmark Tests project’s (NBTP) QL test written by a large cohort of prospective applicants to higher education, in order to contribute to this understanding. A large proportion of these candidates were unable to cope with quantitative literacy demands of the kinds commonly encountered in higher education. More than half of candidates need some kind of supplementary QL support and at least 30% require extensive support. Candidates’ performance on subgroups of the QL test items and on individual items provides further insights into particular strengths and weaknesses. The results highlight that opportunities for the development of QL competencies should be found and these should be integrated into disciplinary teaching.